Pengaruh Pengungkapan Biaya Lingkungan terhadap Kinerja Keuangan dengan Kinerja Lingkungan sebagai Variabel Moderasi - Naufal Mahdy Ramadhana; Mia Angelina Setiawan (Universitas Negeri Padang, 2024)
The aim of this research is to empirically test the positive influence of environmental cost disclosure on the company financial performance. And examine how environmental performance strengthens the positive relationship of environmental cost disclosure on financial performance. The type of research used is causative research. This research collects research data by means of library research. Literature studies are obtained from literature that is relate to the problem to be research. In this research, data was collected using documentation method. The research sample was 36 manufacture and mining company listed on the Indonesia stock exchange, selected using a purposive sampling technique method, where the population criteria selected were companies registered in 2014 until 2018. SPSS v.22 was used to distribute data and processed and then tested the hypothesis in this research. The conclusion obtained from this research is that environmental cost disclosure does have a positive effect on financial performance. Then for next hypothesis, environmental performance strengthens the negative influence of environmental cost disclosure on financial performance.